Epithelial-derived galectin-9 containing exosomes contribute to the immunomodulatory effects promoted by 2’-fucosyllactose and short-chain galacto- and long-chain fructo-oligosaccharides - Ayechu-Muruzabal, Veronica; de Boer, Merel; Blokhuis, Bart; Berends, Alinda J.; Garssen, Johan; Kraneveld, Aletta D.; van’t Land, Belinda; Willemsen, Linette E. M. (Frontiers in Immunology, 2022)
Early life exposure to non-digestible oligosaccharides (NDO) or microbial components is known to affect immune development. NDO in combination with a TLR9 agonist mimicking bacterial triggers (CpG) promoted the secretion of galectins through unknown pathways. We aimed to study the contribution of exosomes in epithelial galectin secretion and subsequent immunoregulation upon exposure to a mixture of NDO by inhibiting exosome biogenesis. Human intestinal epithelial cells (IEC) (FHs 74 Int or HT-29) were apically exposed to 2’-fucosyllactose (2’FL) and short-chain galacto- and long-chain fructo-oligosaccharides (GF), alone or with CpG. Basolaterally, non-activated or αCD3/CD28-activated peripheral blood mononuclear cells (PBMC) were added. After 24 h incubation, IEC were washed and incubated in fresh medium to analyze epithelial-derived galectin secretion. Additionally, before exposure to NDO and CpG, IEC were exposed to GW4869 to inhibit exosome biogenesis. After 24 h of incubation, IEC were washed and incubated for additional 24 h in the presence of GW4869, after which epithelial-derived galectin secretion was studied. Also, epithelial-derived exosomes were isolated to study the presence of galectins within the exosomes. Compared to CpG alone, exposure to 2’FL/GF mixture and CpG, significantly enhanced Th1-type IFN and regulatory IL-10, and decreased IL-13 secretion, while increasing IEC-derived galectin-9 secretion in the HT-29/PBMC model. Similarly, in the FHs 74 Int/PBMC co-culture, 2’FL/GF induced immunomodulatory effects in the absence of CpG. Interestingly, galectin-9 and -4 were present in CD63-expressing exosomes isolated from HT-29 supernatants after IEC/PBMC co-culture. Exposure to GW4869 suppressed 2’FL/GF and CpG induced epithelial-derived galectin-9 and -4 secretion, which subsequently prevented the rise in IL-10 and reduction in IL-13 secretion observed in the HT-29/PBMC co-culture model upon exposure to 2’FL/GF and CpG. Exposure to 2’FL/GF and CpG or 2’FL/GF promoted Th1-type regulatory effects in HT-29/PBMC or FHs 74 Int/PBMC co-culture respectively, while Th2-type IL-13 was reduced in association with increased galectin-9 release. Galectin-9 and -4 were present in exosomes from HT-29 and the inhibition of exosome biogenesis inhibited epithelial-derived galectin secretion. This, also affected Immunomodulatory effects in IEC/PBMC co-culture suggesting a key role of galectin expressing IEC-derived exosomes in the mucosal immune regulation induced by NDO.